2023
DOI: 10.3390/ijms241411470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin 1-7 and Mas Receptor Agonist on Renal System in a Rat Model of Heart Failure

Abstract: Congestive heart failure (CHF) is often associated with impaired kidney function. Over- activation of the renin–angiotensin–aldosterone system (RAAS) contributes to avid salt/water retention and cardiac hypertrophy in CHF. While the deleterious effects of angiotensin II (Ang II) in CHF are well established, the biological actions of angiotensin 1-7 (Ang 1-7) are not fully characterized. In this study, we assessed the acute effects of Ang 1-7 (0.3, 3, 30 and 300 ng/kg/min, IV) on urinary flow (UF), urinary Na+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…A strong link between congestive heart failure (CHF) and kidney function has been already described [128]. Exploring the role of Ang 1-7 in this context, it was found that chronic infusion of Ang 1-7 (or AVE0991) increases urinary sodium and potassium excretion, urinary cGMP, and reduced serum creatinine and aldosterone levels in rats who underwent placement of aortocaval fistula as a model of CHF compared to controls, evidencing the important role of the heptapeptide in CHF kidney function [107].…”
Section: Kidneymentioning
confidence: 82%
See 1 more Smart Citation
“…A strong link between congestive heart failure (CHF) and kidney function has been already described [128]. Exploring the role of Ang 1-7 in this context, it was found that chronic infusion of Ang 1-7 (or AVE0991) increases urinary sodium and potassium excretion, urinary cGMP, and reduced serum creatinine and aldosterone levels in rats who underwent placement of aortocaval fistula as a model of CHF compared to controls, evidencing the important role of the heptapeptide in CHF kidney function [107].…”
Section: Kidneymentioning
confidence: 82%
“…The beneficial role of Ang 1-7 in the heart has been widely described [104][105][106]. Chronic infusion of Ang 1-7 in a rat model for heart failure has been shown to preserve cardiac function, coronary perfusion, and aortic endothelial function [104], reduce cardiac hypertrophy [107], and strongly reduce Ang II levels in the heart of control Ang 1-7 infused rats [108]. Moreover, Ang 1-7 strongly prevents cardiac remodeling induced by Ang II [109].…”
Section: Heartmentioning
confidence: 98%
“…While the adverse effects of angiotensin II (Ang II) in HF are well established, the biological actions of angiotensin 1-7 (Ang 1-7) are less clear. Chronic administration of Ang 1-7 or its agonist AVE 0991 exerted important diuretic, natriuretic and kaliuretic effects in HF rats, but not in sham controls [63]. Serum creatinine and aldosterone concentrations were much higher in vehicle-treated HF rats vs. controls.…”
Section: Countering Raasmentioning
confidence: 87%